2021
DOI: 10.1177/00048674211043047
|View full text |Cite|
|
Sign up to set email alerts
|

The evidence is in: Repetitive transcranial magnetic stimulation is an effective, safe and well-tolerated treatment for patients with major depressive disorder

Abstract: Despite more than 25 years of research establishing the antidepressant efficacy of repetitive transcranial magnetic stimulation, there remains uncertainty about the depth and breadth of this evidence base, resulting in confusion as to where repetitive transcranial magnetic stimulation fits in the therapeutic armamentarium in the management of patients with mood disorders. The purpose of this article is to provide a concise description of the evidence base supporting the use of repetitive transcranial magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…The authors support these claims only by references to the same lead author’s previous publications and with no systematic review of the evidence. As has been presented recently in this journal (Fitzgerald et al, 2021a) and described extensively elsewhere (e.g. Brunoni et al, 2017; Papadimitropoulou et al, 2017; Razza et al, 2020), these statements are inaccurate (see Table 1).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…The authors support these claims only by references to the same lead author’s previous publications and with no systematic review of the evidence. As has been presented recently in this journal (Fitzgerald et al, 2021a) and described extensively elsewhere (e.g. Brunoni et al, 2017; Papadimitropoulou et al, 2017; Razza et al, 2020), these statements are inaccurate (see Table 1).…”
mentioning
confidence: 90%
“…Brunoni et al, 2017; Papadimitropoulou et al, 2017; Razza et al, 2020), these statements are inaccurate (see Table 1). In fact, there already exists a substantive evidence base supporting the use of rTMS in the treatment of depression that extends from multisite clinical trials to multiple meta-analyses, network meta-analyses, umbrella reviews and large-scale real-world treatment outcome data (Fitzgerald et al, 2021a). Scientific support for the efficacy and cost-effectiveness of rTMS for depression is by no means in ‘ its infancy ’: in fact it is consistent with that required to support the clinical use of a new treatment and is underwritten by a wealth of data exploring its neurobiological mechanisms (Luan et al, 2020) and real-world outcomes (Sackeim et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20][21] Multiple randomized, sham-controlled trials and meta-analyses have established rTMS as an evidence-based therapy for TRD. [22][23][24][25] In large, real-world studies, treatment response rates to rTMS of 50-80% have been reported. [26][27][28][29] The physiological and hence therapeutic effects of rTMS are determined by the stimulation protocol, consisting of the stimulation target, frequency/pattern and intensity of the stimulation pulses applied, the number of pulses applied per stimulation session, and the number of sessions applied over a course of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…rTMS involves the repeated application of electromagnetic pulses delivered by a magnetic coil placed on the scalp to depolarize cortical neurons and modulate neuronal activity 17–21 . Multiple randomized, sham-controlled trials and meta-analyses have established rTMS as an evidence-based therapy for TRD 22–25 . In large, real-world studies, treatment response rates to rTMS of 50–80% have been reported 26–29 .…”
Section: Introductionmentioning
confidence: 99%